Experimental analysis of aluminium/carbon epoxy hybrid laminates under flexural load (Fracture and Structural Integrity, 2019)
Industry needs new materials that present very high structural characteristic, such as high strength, low weight and high damage tolerance. To obtain these characteristics a new class of materials has been introduced: Fibre Metal Laminate (FML); they consist in metal sheets alternated to composite material layers: in such manner, the good characteristics of each constituent material confer the utmost properties to the FMLs. However, the mechanical properties depend, among other factors, on the thickness and the numerousness of the layers constituting the FML, as well as the interface between metal and composite. Therefore, in this paper, the influence of the abovementioned factors on the material answer to flexural load was investigated. In particular, different kinds of laminates were produced varying the layers adhesion and the layers thickness, but maintaining unaltered the metal/composite volume ratio and the total laminate thickness. Then their structural behaviour was investigated through three-point bending test, and it was found that the flexural behaviour was affected by both the investigated factors; in fact, the maximum flexural load diminished incrementing the number of layers and inserting an adhesive layer at the metal/composite interface.
Keywords: Fibre metal laminate; flexural load; structural behaviour